Informing patients about their mutation tests: CDKN2A c.256G>A in melanoma as an example - Hemminki, Kari; Srivastava, Aayushi; Rachakonda, Sivaramakrishna; Bandapalli, Obul; Nagore, Eduardo; Hemminki, Akseli; Kumar, Rajiv (Hereditary cancer in clinical practice, 2020)
BACKGROUND: When germline mutations are suspected as causal in cancer, patient DNA may be sequenced to detect variants in relevant genes. If a particular mutation has not been reported in reliable family studies, genetic counselors are facing a dilemma of appropriately informing patients. Many sequencing facilities provide an interpretation of the findings based on the available sequence databases or on prediction tools that are curated from bioinformatics and mechanistic datasets. The counseling dilemma is exacerbated if the pedigree data are not informative but the in silico predictions suggest pathogenicity. METHODS: We present here a real world example of the c.256G > A CDKN2A variant, which was detected in one melanoma patient where two siblings were diagnosed with melanoma in situ. We investigated a detailed family history of the affected siblings in order to survey probability of the cancer risks within the context to this mutation. RESULTS: This c.256G > A CDKN2A variant was detected in one of the brothers and in the melanoma-free mother while the other brother in the family tested negative. The variant had been previously described in one patient from a melanoma family. In the family under investigation, the mother's 16 first-and second-degree relatives had survived past the median onset age for melanoma and none presented melanoma. We tested the variant using multiple bioinformatic tools that all predicted deleteriousness of the variant. The genetic counseling report to the melanoma patient stated that the CDKN2A variant was 'likely pathogenic' and the disease was defined as 'likely hereditary melanoma'. CONCLUSIONS: The pedigree data showed at the most a low penetrance variant, which, if taken into consideration, might have altered the provided diagnosis. When dealing with 'practically' unknown variants the counselors would be advised to incorporate a detailed family history rather than basing predictions on functionality provided by sequencing facilities.
Keywords: Functionality; Genetic counseling; Deleteriousness; Melanoma suppressor gene